US Right of Veto Against UN Resolution on Terrorism of ISIS Foreign Militias - Tsabitah, Annisa Farras; Luthfi, Khoirur Rizal (Law Research Review Quarterly, 2021)
This article analyzes how the US proposes a Veto Rights against a resolution issued by the United Nations against anti-terrorism, namely the Persecution, Reintegration, and Rehabilitation system for foreign ISIS militants who are stranded in Syrian camps. How was the veto issued by the United States against ISIS detention without a Veto provision based on the UDHR, International Humanitarian Law, and also the 1949 Geneva Conventions and Additional Protocols I and II 1977. This research was conducted to see the effect of the US veto on the fate of ISIS militias and the efforts and steps that can be done to solve the ISIS militia problem from the perspective of international law. The research method used was normative juridical. The result of the research was that the PRR resolution against ISIS militias was canceled with the veto power issued by the United States. Efforts that can be made in this regard include (1) continuing to prioritize the role of the PRR against ISIS foreign militants who are in Syrian Camps, focusing on dealing with foreign ISIS militias and countering terrorism through related conventions, such as the Universal Declaration Human Rights (UDHR), the 1949 Geneva Conventions, the 1907 Hague Convention, and the 1977 Additional Protocols I and II, and continue to urge all members of the state and all parties, that all measures taken to combat terrorism must fulfill their obligations under international law, including humanitarian law, international human rights law, and international refugee law with the impact of such actions